2018
DOI: 10.3389/fenrg.2018.00050
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D Printed Porous Copper Anode in Microbial Fuel Cells

Abstract: In this study, 3D printing technique was utilized to fabricate three-dimensional porous electrodes for microbial fuel cells with UV curable resin, followed by copper electroless plating. A maximum voltage of 62.9 ± 2.5 mV and a power density of 6.45 ± 0.5 mWm −2 were achieved for MFCs with 3D printed porous copper (3D-PPC) anodes, which were 8.3-and 12.3-fold higher than copper mesh electrodes, respectively. This illustrated the great advantage of 3D porous anodes in MFCs compared to flat anode structures. Bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…To further illustrate the impacts of copper corrosion on the EMBR performances, the copper ion concentration in the EMBR media was monitored every 4 days during operation. From Figure 4a , it's quite clear that the copper concentration never exceeded 25 μg/L in the EMBR media, which exhibited the excellent anti-corrosion properties of the Cu-HFM cathode in EMBR system and was far less than the amount required for killing bacterial cells (Wu et al, 2010 ; Bian et al, 2018 ; Kimber et al, 2018 ). One point we must mention is that the synthetic wastewater used in our experiment contains copper ions (25.6 μg/L), which served as one trace element for bacterial growth on the anode and in the suspension for COD removal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further illustrate the impacts of copper corrosion on the EMBR performances, the copper ion concentration in the EMBR media was monitored every 4 days during operation. From Figure 4a , it's quite clear that the copper concentration never exceeded 25 μg/L in the EMBR media, which exhibited the excellent anti-corrosion properties of the Cu-HFM cathode in EMBR system and was far less than the amount required for killing bacterial cells (Wu et al, 2010 ; Bian et al, 2018 ; Kimber et al, 2018 ). One point we must mention is that the synthetic wastewater used in our experiment contains copper ions (25.6 μg/L), which served as one trace element for bacterial growth on the anode and in the suspension for COD removal.…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been demonstrated to work efficiently by Myung et al (Myung et al, 2018 ), where copper mesh, serving as one kind of fouling-resistant cathodes in microbial fuel cells (MFCs), experienced far less bio-clogging than stainless steel mesh. Besides, several studies have reported the excellent conductivity of copper electrodes in BES compared with carbon and other metal materials (Baudler et al, 2015 , 2017 ; Bian et al, 2018 ), which could help enhance the current density and reduce the ohmic loss. However, copper-based membrane electrodes and their anti-biofouling performances in the EMBR system were rarely discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The development of electrodes that possess highly porous structures for optimal bacterial adhesion and excellent electrochemical performance for high current output has been of great interest to the MET research communities (Zhou et al, 2017;Bian et al, 2018a;Bian et al, 2018b). Notably, complex macro-porous 3D electrode materials have been found suitable for providing a larger surface area for the biofilm developments and thereby improve the electrochemical performance of METs (Hindatu et al, 2017;Zhou et al, 2017).…”
Section: Electrodesmentioning
confidence: 99%
“…The additive manufacturing (AM) process or threedimensional printing (3DP) has been expanding rapidly in recent years. Briefly, 3DP generates 3D structures from computer-aided design (CAD) models by adding the material layer-by-layer, allowing rapid and precise fabrication of sophisticated structures and devices with complex geometry with minimum human interventions (Geissler and Xia, 2004;Bian et al, 2018b;You et al, 2020). Due to these promising features, 3DP has been implemented in various fields, including industrial prototype printing, aerospace (Griffiths, 2015), medical implants (Murphy and Atala, 2014;Rasperini et al, 2015), and arts (Walters and Davies, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further development for conductive 3D printable materials is needed for AM-built MFCs. An interesting approach to this was made by Bian et al [17], who used non-conductive UV curable resin to print anode structures, and then modified the surface using copper electroless plating. Although copper is highly conductive (1.68 × 10 −6 Ω•cm), it is prone to corrosion in the MFC anode environment, unless external control of the anode potential is applied.…”
Section: Introductionmentioning
confidence: 99%